Small cardamom genome: development and utilization of microsatellite markers from a draft genome sequence of Elettaria cardamomum Maton - Gaikwad, Ambika Baldev; Kumari, Ratna; Yadav, Sheel; Rangan, Parimalan; Wankhede, Dhammaprakash Pandhari; Bhat, KV. (Frontiers in Plant Science, 2023)
Small cardamom (Elettaria cardamomum Maton), the Queen of spices, is the third most expensive spice in the world after saffron and vanilla, valued highly for its aroma and taste. This perennial herbaceous plant is a native of coastal parts of Southern India and displays a significant amount of morphological diversity. Its genetic potential has not been exploited due to lack of genomic resources limiting our understanding of the genome and important metabolic pathways which give it the economic advantage in the spice industry. Here, we report upon the de novo assembled, draft whole genome sequence of cardamom variety, Njallani Green Gold. We used a hybrid assembly strategy using the reads from the Oxford Nanopore, Illumina and 10x Genomics GemCode sequencing chemistries. The assembled genome length was 1.06 GB (gigabases) which is close to the estimated genome size of cardamom. More than 75% of the genome was captured in 8000scaffolds with a N50 of 0.15MB. The genome appears to have a high repeat content and 68055 gene models were predicted. The genome is close to Musa species and displays an expansion and contraction in select gene families. The draft assembly was used for in silico mining of simple sequence repeats (SSRs). A total of 2,50,571 SSRs were identified of which 2,18,270 were perfect SSRs and 32,301 were compound SSRs. Among the perfect SSRs, trinucleotides were most abundant (1,25,329) and hexanucleotide repeats appear least (2,380). From the 2,50,571 SSRs mined, 2,27,808 primer pairs were designed based on flanking sequence information.Wet lab validation was performed for 246 SSR loci and 60 SSR markers were used for diversity analysis of a set of 60 diverse cardamom accessions. The average number of alleles detected per locus were 14.57 with a minimum of 4 and maximum of 30 alleles.The SSR markers identified would help in the development of gene or trait-linked markers which can be subsequently used for marker-assisted breeding for crop improvement in cardamom. The information on utilization of the SSR loci for generation of markers has been developed into a public database, ‘cardamomSSRdb’ that is freely available for use by the cardamom community.